L’atelier du regard - Olivier Ihl (La Nouvelle Revue du Travail)
Abstract : Visual sociology could benefit by taking a closer look at the world of drawings and engravings and not just photography or cinema. By so doing, it would make the graphic world more accessible to a wider audience and turn it into a real space for discovery and knowledge. This is the ambition underlying the present article, which focuses on images of a particular kind and notably the way in which some of the transformations affecting Paris in the 19th century were captured and depicted. Entitled Madame, madame, un sous-jupe à vendre (“Lingerie for sale”), a caricature drawn by Louis Marie Bosredon (1815-1881) is viewed here as a vehicle for revealing social and urban change. Drawn by a working class artist who was a supporter of the socialist Charles Fourier, it was first published in 1857. The research method used here deviates from any strict distinction between art and science in such a ways as to transform working class drawings into fully-fledged vehicles for participant observation.